Rehabilitation Nursing Interventions in the Woman with Pelvic Floor Dysfunction - da Costa Marques Pinto, Vanda Lopes (2022)
Introduction: Within the scope of the competences defined for the rehabilitation specialist nurse, it is observed that they intervene in the woman with pelvic floor dysfunction, a situation with great impact on the person’s life. Therefore, it is important to understand which interventions to implement. Objective: Identify the existing scientific evidence on rehabilitation nursing interventions in the woman with pelvic floor dysfunction. Method: A narrative review was carried out, using the CINAHL and MEDLINE databases via the EBSCO platform, complemented by unpublished literature and reference manuals. Results and Discussion: The consulted literature offers specific indications for the assessment of women with pelvic floor dysfunction, including initial assessment, physical examination, and instruments such as the Modified Oxford Scale and the PERFECT Instrument. As part of the interventions, we identified those in the behavioral sphere, strengthening of the pelvic floor muscles, complementary techniques such as biofeedback and electrostimulation, hypopressive abdominal exercises, relaxation strategies and specific assistive devices. Conclusion: Pelvic floor dysfunction in women is a relevant issue considering the impact it has on the quality of life throughout their life span. In this context, rehabilitation nursing finds an opportunity for intervention, validated by the competences and quality standards defined for this care.